Regulation of corpora allata in females of Pyrrhocoris apterus (Heteroptera) (a mini-review) - Hodková, M; Okuda, T; Wagner, R M (In vitro cellular & developmental biology. Animal, 2001)
Mechanisms for the transduction of photoperiodic and food signals to the corpus allatum (CA) are described. The focus of this paper is on the control of the CA by the brain in adult females of the firebug, Pyrrhocoris apterus. By using surgical interventions to the neuroendocrine complex of brain-subesophageal ganglion-corpora cardiaca-CA (BR-SG-CC-CA) in vivo and in vitro we were able to identify two regulatory pathways. (1) Slow regulation of the CA activity (stimulation or inhibition) needs a relatively long period of time to be accomplished (several d) in vivo and is associated with changes of the gland cell volume and ultrastructure. The stimulated or inhibited activity of the CA is maintained during short-term incubation of the isolated CA in vitro. (2) Fast inhibition of the CA activity is reversible during short-term incubation in vitro; the CA can be switched from lower to higher activity and vice versa, depending on the presence or absence of the BR-SG in the medium. Both slow and fast regulatory factors originate in the pars intercerebralis of the brain and in intact neuroendocrine complex they reach the CA via nerves. A slow inhibitor, induced by short d, causes reproductive diapause. A fast inhibitor prevents ovarian maturation in starved nondiapausing females. A slow stimulator, induced by feeding under long d, overcomes the fast inhibition of the CA, thereby stimulating vitellogenesis. Food signals are transmitted to the brain via humoral pathways.
Keywords: mozek; techniky in vitro; Corpora Allata; Animals; Female; ženské pohlaví; Heteroptera; zvířata; In Vitro Techniques; corpora allata; Brain